How to design compelling Virtual Reality or Augmented Reality experience? - Richir, Simon; Fuchs, Philippe; Lourdeaux, Domitile; Millet, Dominique; Buche, Cédric; Querrec, Ronan (International Journal of Virtual Reality, 2015)
The convergence of technologies currently observed in the field of Virtual Reality, Augmented Reality, robotics and consumer electronic reinforces the trend of new applications appearing every day. But when transferring knowledge acquired from research to businesses, research laboratories are often at a loss because of a lack of knowledge of the design and integration processes in creating an industrial scale product. In fact, the innovation approaches that take a good idea from the laboratory to a successful industrial product are often little known to researchers. The objective of this paper is to present the results of the work of several research teams that have finalized a working method for researchers and manufacturers that allow them to design virtual or augmented reality systems and enable their users to enjoy "a compelling Virtual Reality experience". That approach, called "the I2I method", present 11 phases from "Establishing technological and competitive intelligence and industrial property" to "Improvements" through the "Definition of the Behavioral Interface, Virtual Environment and Behavioral Software Assistance". As a result of the experience gained by various research teams, this design approach benefits from contributions from current Virtual Reality and Augmented Reality research. Our objective is to validate and continuously move such multidisciplinary design team methods forward.